'Saving our order': Thomas Becket and the law. Issue 3 (1st October 2020) - Williams, Rowan
ABSTRACT: The Becket controversy has traditionally been misrepresented as simply a conflict between a universal ideal of the rule of law and the demand of a particular group for certain kinds of immunity. The issue was not only about the secular court's right to judge delinquent clerks, but about rights of appeal and the control of ecclesiastical property for purposes not determined by lay authority. But Becket's belief that such resistance required a doctrine of the freedom of the clergy from lay courts in respect to all their actions (with ecclesiastical courts free to impose penalties aimed at penance and restoration) carries its own problems and helps to shape a clerical culture whose dangerous long-term effects can be seen in the recent child abuse scandals.